Perancangan Sistem Informasi Manajemen Rumah Sakit Modul Akuntansi Dan Keuangan - Hardiwinata, Tantoni; Buana, Putu Wira; Wirdiani, Ni Kadek Ayu (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2015)
Module Management Information System of Accounting and Finance in a hospital is required, because the transactions that occur in a company already so much. Transactions that are not recorded properly, there’s no chance in making judgments and decisions well . Module of Accounting and Finance to increase its benefits, the data must be systematically recorded, summarized and grouped, and presented in the report. Manually recording transactions is still a constraint to get a good recording results because of errors in recording transactions often occur as well as the time required to obtain a sufficiently long financial statements . In this study will be made of a system of management accounting and financial information that is useful to overcome obstacles in the accounting process is done manually. The management system includes recording in journalizing, ledgers, and report generation. The management information system in the form of context diagram, diagram Tiered, Overview Diagram, Data Flow Diagrams, Database, and GUI .